KAJIAN BIOREMEDIASI PADA TANAH TERCEMAR PESTISIDA - Dwi Juli Puspitasari; Kahiruddin Khairuddin (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2016)
The use of pesticides to eradicate pests are an integral part in farming system. Pesticides use to increase production and protect the production of physical defects can also cause pollution on agricultural land. The presence of pesticide residues in soil and agricultural production can cause health problems for human and animals and even death. To overcome this problem there needs a way to degrade hazardous waste in the environment by performing the remediation. Remediation is carried out by microorganisms fungi, bacteria and algae known as bioremediation. Bioremediation aims to transform compounds into harmless compounds with the end result are carbon dioxide, water and biomass cells. The advantages of bioremediation are environmentally friendly, highly efficient, low cost, can be implemented directly in the field, laboratory and combined with chemical and physical methods.Keywords: bioremediation, soil degradation, pesticides, microorganisms